Pseudo Number 0.999… (Indian Journal of Advanced Mathematics (IJAM), 2024)
As we know that the number 0.999… is a rational number and mathematicians, teachers and students of mathematics generally wonder whether the number 0.999… and the number 1 are really equal or not. This problem is one of the ancient problems of mathematics and is generally the most asked problem. While trying to solve the above problem, a new fact is found that the number 0.999… is not a real problem and with this a satisfactory solution of the above problem is obtained. In this paper, we do analysis about the existence of the number 0.999… on the real number line and prove that the number 0.999… is only a virtual number.